Bottlik, Zs., Berki, M. and Jobbitt, S. (eds.): Power and Identity in the Post-Soviet Realm: Geographies of Ethnicity and Nationality after 1991 - WhiteGeorge W. (Hungarian Geographical Bulletin, 2021)
-